Analysis of "Geological Tourism +" Mode and Realization Path Based On Innovation. (January 2019) - Chang, Chen
Abstract: Geological tourism is a basic supporting element and an important format in the development of tourism industry, It is also the development of the domestic tourism of the more systematic, mature and has been widely accepted by the tourists and favourite product type; To all kinds of geological parks or geological scenic spots as the representative of the geological tourism has made rapid development, Also face the bottleneck of their own development; To explore a variety of "Geological tourism +" innovative development model, for the future of geological tourism has a positive exploration of value and practical significance.